2012
DOI: 10.1007/978-3-642-34447-3_21
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Security of Online Payments: A Conceptual Model for a Robust E-Payment Protocol for E-Commerce

Abstract: Abstract. The rapid growth of the Internet and its adoption for commercial transactions is indisputable. However, the core security protocols of the Internet today are susceptible to security lapses, especially when it comes to online payment systems which are indispensable to the growth of e-commerce across the globe. This has led to the development of various online payment protocols to ensure the security of online transactions such as Secure Electronic Transaction and The Secure Socket Layer. In designing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Recently, the secure wireless transactionschemehas turned into a research extent towards payment system.Some of them have concentrated towards security and privacy issues alone such as Ray et al [14], Kouta et al [15], Cui et al [16], Tiwari et al [17],Raghuwanshi et al [18], Abdellaoui and Pasquet [19], Mazumdar and Giri [20], Takyi and Gyaase [21],Lawal et al [22],Khan et al [5],Aigbe and Akpojaro [23],Kim et al [24]. On the other hand, focused on secure mobile payment system [25]- [30]and some of them have focused Secure Electronic Transaction protocol [31]- [33].Those are discussed as follows.…”
Section: A Need For the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the secure wireless transactionschemehas turned into a research extent towards payment system.Some of them have concentrated towards security and privacy issues alone such as Ray et al [14], Kouta et al [15], Cui et al [16], Tiwari et al [17],Raghuwanshi et al [18], Abdellaoui and Pasquet [19], Mazumdar and Giri [20], Takyi and Gyaase [21],Lawal et al [22],Khan et al [5],Aigbe and Akpojaro [23],Kim et al [24]. On the other hand, focused on secure mobile payment system [25]- [30]and some of them have focused Secure Electronic Transaction protocol [31]- [33].Those are discussed as follows.…”
Section: A Need For the Studymentioning
confidence: 99%
“…Takyi and Gyaase [21]suggested that Robust Electronic Payment Protocol (REPP) fares better when compared theoretically with live cardholder verification in terms of security, usability, verification of cardholder and execution. But, the REPP authenticates the merchant just as SET does.…”
Section: Studies Related To Security Privacy and Encryptionmentioning
confidence: 99%
“…The popular commercial activities, especially on the internet, has gained maximum prominence in the field of commerce as more and more goods and services are seen on the internet daily for online transactions. Buying and selling online, also known as e-commerce, is efficient, easy, reliable and convenient (Takyi and Gyaase, 2012). In order to have reliable e-commerce services, there must be digital measures in place to check the security of users to ensure safety in online transactions with access control measures such as authentication and others measures like privacy, integrity and non-repudiation.…”
Section: Introductionmentioning
confidence: 99%
“…The payments for online transactions are made either with a credit card, debit card, or direct bank payment. The payment process poses some level of risk because the entire payment procedures are susceptible to cyber-attack (Strategy, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation